Health service utilization in immigrants with multiple sclerosis. - Dalia L Rotstein; Ruth Ann Marrie; Karen Tu; Susan E Schultz; Kinwah Fung; Colleen J Maxwell (PLoS ONE)
Background Access to neurology specialty care can influence outcomes in individuals with multiple sclerosis (MS), but may vary based on patient sociodemographic characteristics, including immigration status. Objective To compare health services utilization in the year of MS diagnosis, one year before diagnosis and two years after diagnosis in immigrants versus long-term residents in Ontario, Canada. Methods We identified incident cases of MS among adults aged 20-65 years by applying a validated algorithm to health administrative data in Ontario, Canada, a region with universal health insurance and comprehensive coverage. We separately assessed hospitalizations, emergency department (ED) visits, outpatient neurology visits, other outpatient specialty visits, and primary care visits. We compared rates of health service use in immigrants versus long-term residents using negative binomial regression models with generalized estimating equations adjusted for age, sex, socioeconomic status, urban/rural residence, MS diagnosis calendar year, and comorbidity burden. Results From 2003 to 2014, there were 13,028 incident MS cases in Ontario, of whom 1,070 (8.2%) were immigrants. As compared to long-term residents, rates of hospitalization were similar (Adjusted rate ratio (ARR) 0.86; 95% CI: 0.73-1.01) in immigrants the year before MS diagnosis, but outpatient neurology visits (ARR 0.93; 95% CI: 0.87-0.99) were slightly less frequent. However, immigrants had higher rates of hospitalization during the diagnosis year (ARR 1.20, 95% CI: 1.04-1.39), and had greater use of outpatient neurology (ARR 1.17, 95% CI: 1.12-1.23) but fewer ED visits (ARR 0.86; 95% CI: 0.78-0.96). In the first post-diagnosis year, immigrants continued to have greater numbers of outpatient neurology visits (ARR 1.16; 95% CI: 1.10-1.23), but had fewer hospitalizations (ARR 0.79; 95% CI: 0.67-0.94). Conclusions Overall, our findings were reassuring concerning health services access for immigrants with MS in Ontario, a publicly funded health care system. However, immigrants were more likely to be hospitalized despite greater use of outpatient neurology care in the year of MS diagnosis. Reasons for this may include more severe disease presentation or lack of social support among immigrants and warrant further investigation.